Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria. (University of Salzburg, 2013)
The Department of Sport Science at the University of Salzburg are proud to present the Abstract Book of the VI International Congress on Science and Skiing (ICSS 2013), held in St. Christoph a. Arlberg, Austria, from December 14 - 19, 2013. The scientific programme offers you a broad interdisciplinary spectrum of current research in Nordic and Alpine skiing and snowboarding. The highlights of the congress will be the five keynotes, presented by George A. Brooks (USA), Albert Gollhofer (DEU) / Jörg Spörri (AUT), H-C. Holmberg (SWE), Hans Hoppeler (CHE) / Josef Kröll (AUT) and Christian Raschner (AUT). The abstract book also includes 103 oral and 63 poster presentations. The entire scope of relevant topics in skiing will be covered by these presentations. In order to maintain a high scientific standard required of this congress, a peer review process was utilized in the selection of the papers. Each abstract was sent to at least one member of the scientific committee to be reviewed. The papers were examined regarding content, topics and structure according to the guidelines of ICSS. Most of the abstracts could be accepted, some of them were accepted after minor improvements, and about ten per cent had to be rejected. ... In addition to the abstract book the Proceedings will be published by Meyer&Meyer in 2014. (Preface of the book)